GENDER OF NOUNS - Eshonkulova Adolat Khaidarovna (Scholar Express Journal, 2021)
The main grammatical feature that is inherent in almost every part of speech is the gender category. How many genders do nouns have and how to correctly define this category for this part of speech? You will find answers to these and other questions in the article
Keywords: Factor; root; reputation; case; determinant